Distribution of the maximum of the Chentsov random field - Kruglova, N. (Інститут математики НАН України, 2008)
Let D = [0, 1]^2 and X(s, t), (s, t) belongs D, be a two-parameter Chentsov random field. The aim of this paper is to find the probability distribution of the maximum of X(s, t) on a class of polygonal lines.